Comparison of bioconcentration and kinetics of GenX in tilapia Oreochromis mossambicus in fresh and brackish water. (January 2022) - Siddiqui, Samreen; Fitzwater, Mason; Scarpa, John; Conkle, Jeremy L.
Abstract: Contaminants of emerging concern (CEC) are a broad suite of chemicals commonly found in the environment, aquatic organisms and even drinking water. They include pharmaceuticals, personal care products, industrial chemicals and compounds added to consumer products. The CEC ammonium 2, 3, 3, 3-tetrafluoro-2-heptafluoropropoxy propanoic acid, which is more commonly known as generic name GenX, is a replacement of common processing aid longer chain perfluorinated compounds (PFAS) due to a manufacturing shift in 2002 following the EPA stewardship program of 2015/16 in USA (USEPA, 2006). However, recently reported in North Carolina drinking water, GenX raising concerns about its accumulation in aquatic organisms, both wild and cultured, which could be a pathway for human exposure. To examine GenX accumulation and potential for human exposure, tilapia ( Oreochromis mossambicus) fingerlings were dosed with GenX for up to 96 h in fresh (0 ppt) or brackish (16 ppt) water to determine uptake and bioconcentration. Depuration values were also determined after a 96 h exposure followed by 96 h without exposure. Bioconcentration was in decreasing order of plasma > liver > carcass > muscle, with higher distribution to liver followed by carcass and muscle. Muscle was found to have the highest half-life (1278 h) followed by carcass (532 h), plasma (106 h), and liver (152 h). The rate of uptake and depuration was positively affected by the salinity. As bioconcentration in all tissues increased with increasing salinity, this may raise concern for marine organisms and human exposure. Graphical abstract: Image 1 Highlights: GenX accumulated in all tissues examined. The highest accumulation was found in the liver. Higher salinity increased bioaccumulation. Higher salinity resulted in shorter GenX half-lives in tilapia. GenX persistence was highest in the tilapia fillet (30–54 days) indicating a preference for protein binding.